Review on Ethical Hacking and its Relationship with Artificial Intelligence - Ardila Osma, Javier Andrés
This document provides an overview of the main characteristics of ethical hacking processes as a computer security tool applying artificial intelligence (AI), taking into account that the adoption of information protection strategies in organizations is no longer a luxury that only some adopt, but practically a requirement that takes into account the need to counteract risks in local networks and the Internet. AI is a technological paradigm that is increasingly used in industry and organizations to support their processes and has become so relevant that refusing to use it will imply significant difficulties in the medium term to keep up with the demands and not stay relegated from the future. The structure of the document is made up of several sections, first the definition and the historical origin of hacking and ethical hacking are presented, then the concept of artificial intelligence and its relationship with ethical hacking, its most used algorithms and its advantages and disadvantages. Disadvantages The current context of ethical hacking at global and local level, as well as its regulatory framework, is detailed below; then the main vulnerabilities detected in ethical hacking are mentioned, brief recommendations are presented and finally the most relevant conclusions are shown.